A Study of User Perception, Interface Performance, and Actual Usage of Mobile Pedestrian Navigation Aides. (September 2013) - Wen, James; Helton, William S.; Billinghurst, Mark
The proliferation of pedestrian navigation tools has made it challenging for users to avoid being confused and overwhelmed by the choices. Studies comparing mobile pedestrian navigation aides have generally based conclusions on either survey results from separate trials of exclusive interface usage or on performance of the interfaces as judged by the speed with which users are able to complete wayfinding tasks. However, it is not clear if users would mirror their individual trials or find a more strategic mixed-mode approach to using the tools at their disposal when given an option to choose from a set of tools. It is also unclear if users actually care about performance when choosing a navigation tool. We conducted a study to compare actual usage of navigation tools against user perception of the tools and performance with the tools in a series of wayfinding tasks. Results indicate that independent surveys can align well with extreme cases while performance may not actually be a good indicator of usage preferences.